Generalized Health Impact of Social and Material Deprivation on Perinatal Outcomes In Nova Scotia, Canada. (1st June 2016) - Orkin, J; O'Campo, P; Shankardass, K; Dodds, L; Joseph, KS; Allen, V
Abstract: BACKGROUND: Poverty is associated with multiple adverse perinatal outcomes including low birth weight, small for gestational age, pregnancy induced hypertension, gestational diabetes as well as an increased risk for neonatal death. Recent research has attempted to align social theory (i.e., that adverse social exposures impact multiple outcomes) with new statistical modeling that reflects this theory. The Generalized Health Impact (GHI) model looks at the impact on a myriad of adverse outcomes of exposure to negative social risk factor such as low income or poverty. Growing research examines how multiple perinatal outcomes are influenced by social and material deprivation. In particular, having a lower social and economic position in society (socioeconomic position) or being raised in low-income setting has been independently linked to multiple negative health outcomes. OBJECTIVES: To understand the generalized health impact (GHI) on perinatal health for mothers and their children that socioeconomic position (SEP) can have on health. DESIGN/METHODS: Data from the Nova Scotia Atlee Perinatal Database was used. A partnership with Statistics Canada facilitated a confidential linkage with income tax information for the year in which delivery occurred. Multiple logistic regression models were used to examine the relationship between multiple indicators of family income and multiple adverse perinatal and maternal outcomes. In the second stage of analysis, multinomial logistic regression was used to examine effects on a tally of the number of adverse outcomes (0, 1, 2 or ≥3). The study was approved by the IWK Health Centre Research Ethics Board. RESULTS: 117 734 individuals were included. Total family income was less than $23 587 in approximately 62% of families. Effect of low socioeco-nomic position on concomitant adverse perinatal health outcomes was seen with the risk of having 3 or more conditions was highest amongst single mothers (PR 3.1 CI: 2.92-3.27) and families reported as having an income below the low income cut off (PR 2.33 CI:2.16-2.51). Higher material deprivation in the neighbourhood of residence was associated with increased risk of multiple negative perinatal outcomes including pre-term birth and small for gestational age. CONCLUSION: This study highlights the importance of understanding the cumulative effect of SEP on generalized health outcomes for negative perinatal health outcomes. This research should inform clinical practice to recognize that social determinants of health and negative health outcomes occur not in isolation but as a collective. Further research on adequate screening for poverty and clinical assessment of social determinants of health is required.